2017
DOI: 10.3390/nu9111262
|View full text |Cite
|
Sign up to set email alerts
|

WNT Inhibitory Activity of Malus Pumila miller cv Annurca and Malus domestica cv Limoncella Apple Extracts on Human Colon-Rectal Cells Carrying Familial Adenomatous Polyposis Mutations

Abstract: Inhibitors of the Wingless-related Integration site (WNT)/β-catenin pathway have recently been under consideration as potential chemopreventive agents against Familial Adenomatous Polyposis (FAP). This autosomal-dominant syndrome is caused by germline mutations in the gene coding for the protein APC and leads to hyperactivation of the WNT/β-catenin signaling pathway, uncontrolled intestinal cell proliferation and formation of adenocarcinomas. The aim of the present work was to: (i) test, on in vitro cultures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…The Polyphenolic fraction of Annurca contains hundreds of different metabolites [ 26 , 53 ]. The activity of most of the polyphenols contained in AAE is drastically reduced when they are isolated from the extract and used as pure molecules [ 54 ]. AAE phytocomplex seems to represent the perfect environment where polyphenols can exert their biological function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Polyphenolic fraction of Annurca contains hundreds of different metabolites [ 26 , 53 ]. The activity of most of the polyphenols contained in AAE is drastically reduced when they are isolated from the extract and used as pure molecules [ 54 ]. AAE phytocomplex seems to represent the perfect environment where polyphenols can exert their biological function.…”
Section: Discussionmentioning
confidence: 99%
“…The phytocomplex probably acts chemically, by protecting apple metabolites from oxidation and degradation. Recent evidences may suggest that the phytocomplex may as well act biologically by activating and deactivating specific cellular pathways, ultimately augmenting the efficacy of the active metabolites [ 54 ]. In this scenario, the need to follow hundreds of compounds simultaneously increases the complexity of any study aiming at the identification of the mechanism of action of nutraceuticals.…”
Section: Discussionmentioning
confidence: 99%
“…As protein oxidation can be associated with an increased susceptibility to proteases, the antioxidant potential of AMS can be an important player for the keratinization process [52]. Moreover, based primarily on the polyphenolic pool of the Annurca apple extract, it has recently been suggested that there is a biological interference with the WNT signaling, which deserves further investigations according to its critical role in hair cell specification and development [53].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Apples or apple products (apple juice, extracts, dehydrated apples) could exert biological effects to prevent or reduce the proliferation of colorectal cancer, both in in vitro and in vivo models and in case-control studies, by which the risk of colorectal cancer risk resulted inversely correlated with the number of consumed apples. [8][9][10][11][12][13] Those beneficial effects have been attributed to the apple's bioactive molecule mixture, which is more effective than a single bioactive molecule in exerting their biological activities. [14][15][16] We have demonstrated that a specific apple is particularly rich in polyphenols and that its juice leads to the strongest antiproliferative activity against breast cancer cells, in comparison to the five other apple varieties, suggesting that polyphenols play an important role.…”
Section: Introductionmentioning
confidence: 99%